Demineralization and sectioning of human kidney stones: A molecular investigation revealing the spatial heterogeneity of the stone matrix. Issue 1 (6th January 2021) - Canela, Victor Hugo; Bledsoe, Sharon B.; Lingeman, James E.; Gerber, Glenn; Worcester, Elaine M.; El‐Achkar, Tarek M.; Williams, James C.
Abstract: The molecular mechanisms by which kidney stones grow are largely unknown. Organic molecules from the urine combine with mineral crystals to form stones, but analysis of the stone matrix has revealed over a thousand different proteins, with no clues as to which are important for stone growth. Molecules that are present in every layer of a stone would be candidates for having an essential function, and thus the analysis of the stone matrix at a microscopic level is necessary. For this purpose, kidney stones were demineralized, sectioned, stained, and imaged by microscopy, using micro CT for precise orientation. Histological staining demonstrated heterogeneity in the density of adjacent layers within stones. Additional results also showed brilliant and unique autofluorescence patterns in decalcified nephroliths, indicating heterogeneous organic composition in adjacent layers. Regions of calcium oxalate (CaOx) stones were dissected using laser microdissection (LMD) for protein analysis. LMD of broad regions of demineralized CaOx stone sections yielded the same proteins as those found in different specimens of pulverized CaOx stones. These innovative methodologies will allow spatial mapping of protein composition within the heterogeneous stone matrix. Proteins that consistently coincide spatially with mineral deposition would be candidates for molecules essential for stone growth. This kind of analysis will be required to assess which of the thousand proteins in the stone matrix may be fundamental for stone growth. Abstract : Our innovative methodology describes a novel laboratory method to study human kidney stones, whereby the stone matrix is microscopically analyzed to reveal its molecular spatial heterogeneity. It is our intent that the data presented in this manuscript will foster future molecular interrogations into the stone matrix for a better understanding of the underlying mechanisms contributing to renal stone formation.